State and Sources of Knowledge of Pedagogy Students About Current Events Concerning Natural Environment and Its Protection - Ciążela, Ariadna (Studia Ecologiae et Bioethicae, 2021)
The aim of the article is to present results of a study on the knowledge of pedagogy students about latest events and trends concerning natural environments and its protection. Pedagogy students are future teachers supposed to teach their students about such issues. The study was conducted online in May and June 2020. The research group consisted of 140 pedagogy students of The Maria Grzegorzewska University. The aim of the study was not only to check the level of knowledge of pedagogy students, but also to check what are their sources of information about the environment protection. The level of knowledge appeared to be differentiated. 70-80% of participants answered correctly to some questions in the questionnaire, but there were also questions that only less than 40% of participants answered correctly. The results are rather worrying when it comes to the sources of information. Social media appeared to be the main source of information about environment protection for pedagogy students, more important source than news websites or television. Only few participants declared that they learn about environment protection at school or university. The results of the study provoke to reflection about formal environmental education in Poland.